Stewart-Treves Syndrome on the Lower Extremity Associated to Idiopathic Chronic Lymphedema Visualized on FDG PET/CT. (December 2017) - Brittain, Jane Maestri; Nymark, Tine; Hildebrandt, Malene Grubbe; Hovgaard, Dorrit; Andersen, Kim Francis
Abstract : Abstract: Angiosarcomas are highly malignant and rare tumors of vascular or lymphatic endothelial cell origin with a poor prognosis. Lymphangiosarcoma associated with chronic lymphedema is known as Stewart-Treves syndrome. Stewart-Treves syndrome is primarily described in patients with lymphedema of an upper extremity occurring after breast cancer surgery including radical axillary lymph node dissection and subsequent radiotherapy. It is rarely described in the presence of idiopathic chronic lymphedema of the lower extremities. We present a case of lymphangiosarcoma visualized on 18 F-FDG PET/CT, where Stewart-Treves syndrome is secondary to probably a combination of idiopathic chronic lymphedema of the lower extremities and systemic immunosuppressive treatment.